A non‐fluorescent immunohistochemistry method for measuring autophagy flux using MAP1LC3/LC3 and SQSTM1 as core markers - Shahla Shojaei; Amir Barzegar Behrooz; Marco Cordani; Mahmoud Aghaei; Negar Azarpira; Daniel J. Klionsky; Saeid Ghavami (FEBS Open Bio)
Macroautophagy/autophagy is a crucial cellular process for degrading and recycling damaged proteins and organelles, playing a significant role in diseases such as cancer and neurodegeneration. Evaluating autophagy flux, which tracks autophagosome formation, maturation, and degradation, is essential for understanding disease mechanisms. Current fluorescence‐based methods are resource‐intensive, requiring advanced equipment and expertise, limiting their use in clinical laboratories. Here, we introduce a non‐fluorescent immunohistochemistry (IHC) method using MAP1LC3/LC3 and SQSTM1 as core markers for autophagy flux assessment. LC3 levels reflect autophagosome formation, whereas SQSTM1 degradation and a decrease in the number of its puncta indicate active flux (i.e., lysosomal turnover). We optimized chromogenic detection using diaminobenzidine (DAB) staining and developed a scoring system based on puncta number and the percentage of stained cells. This accessible, cost‐effective method enables reliable autophagy quantification using a standard light microscope, bridging the gap between experimental research and clinical diagnostics. Our protocol allows accurate autophagy evaluation in fixed tissues, offering practical applications in biomedical research and clinical pathology assessment.